Piano Sonata no. 1 in F minor, op. 2, no. 1 (Artaria, ca. 1830) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Artaria et Comp.; Austria; Vienna)
Early edition of the Piano Sonata in F minor, op. 2, no. 1, published by Artaria ca. 1830 in a new edition in upright format.i